Processing of German noun plurals: Evidence for first- and second-order schemata. (March 2021) - Köpcke, Klaus-Michael; Schimke, Sarah; Wecker, Verena
Abstract : This article addresses the question of how morphologically complex words are represented in the mental grammar of monolingual adult speakers of German. We contend that in perception, speakers assign a plural or singular meaning according to the degree of reliability to which a given shape is associated with the function singular or plural. In this article, we present the results of two lexical decision experiments with nonce words. In experiment 1, the nonce words presented are preceded by the article form die, and, in experiment 2, the same nonce words are presented as bare nouns. It turns out that the results for experiment 1 and 2 differ. Nevertheless, we argue that the results for both experiments can straightforwardly be explained by a schema account. More precisely, we distinguish between first- and second-order schemata. First-order schemata rely on the pure word form onto which a specific function is mapped. But, recent developments of the schema approach argue that in the speaker's representation of word forms not only single schemata are stored and mapped onto specific functions, but rather schema-pairs, e.g. a singular and its most likely plural partner, referred to as 'second-order schema'. The results of our experiments support the assumption of first- and second-order schemata and their interaction.